Food-borne and water-borne diseases under climate change in low- and middle-income countries: Further efforts needed for reducing environmental health exposure risks - Cissé, Guéladio (Acta tropica, 2019)
Food- and water-borne diseases (FWBD) are among climate and environmental sensitive infectious diseases. Climate change can highly exacerbate FWBD through vulnerable water systems. [Display omitted] •Food- and water-borne diseases (FWBD) are a major cause of mortality and morbidity.•Africa counts 91 million people falling ill and 137,000 dying per year by FWBD.•Climate change could increase FWBD through bad water, sanitation and hygiene (WASH).•Floods’ vulnerability maps of drinking water systems are important for prevention.•Appropriate WASH interventions can significantly contribute in reducing FWBD under climate change. This paper provides a view of the major facts and figures related to infectious diseases with a focus on food-borne and water-borne diseases and their link with environmental factors and climate change. The global burden of food-borne diseases for 31 selected hazards was estimated by the World Health Organization at 33 million disability-adjusted life years (DALYs) in 2010 with 40% of this burden concentrated among children under 5 years of age. The highest burden per population of food-borne diseases is found in Africa, followed by Southeast Asia and the Eastern Mediterranean sub-regions. Unsafe water used for the cleaning and processing of food is a key risk factors contributing to food-borne diseases. The role of quality and quantity of water to the general burden of infectious diseases deserves attention, particularly in low- and middle-income countries, as its effects go beyond the food chain. Water-related infectious diseases are a major cause of mortality and morbidity worldwide, and climate change effects will exacerbate the challenges for the public health sector for both food-borne and water-borne diseases. Selected case studies from Africa and Asia show that (i) climate change extreme events, such as floods, may exacerbate the risks for infectious diseases spreading through water systems, and (ii) improvements related to drinking water, sanitation and hygiene could result in a significant reduction of intestinal parasitic infections among school-aged children. There is a need to better anticipate the impacts of climate change on infectious diseases and fostering multi-stakeholder engagement and multi-sectoral collaborations for integrated interventions at schools, community and household levels. The paper calls for giving priority to improving the environmental conditions affecting food-borne and water-borne infectious diseases under climate change.